Genome editing for the reproduction and remedy of human diseases in mice. Issue 2 (February 2018) - Hara, Satoshi; Takada, Shuji
Abstract With the recent progress in genome-editing technologies, such as the CRISPR/Cas9 system, genetically modified animals carrying nucleotide substitutions or large chromosomal rearrangements can be produced rapidly and at low cost. Such genome-editing techniques have been applied in the generation of animal models, especially mice, for reproducing human disease mutations, such as single-nucleotide polymorphisms (SNPs) or large chromosomal rearrangements identified by genome-wide screening analyses. While application methods are under development for various complex mutations involving genome editing for mimicking human disease-causing mutations in mice, functional studies of mouse models carrying replicated human mutations are gradually being published. In this review, we discuss the recent progress in application methods of the CRISPR/Cas9 system, focusing on the production of mouse models of diseases.